Cloning of endo-β-1,4 glucanase from aspergillus niger and its expression in saccharomyces cerevisiae - Viet Cuong, Pham; Dinh Thi, Quyen; Quyen, Vu Thi; Thi Kim Cuc, Nguyen (Vietnam Journal of Science and Technology, 2017)
Endoglucanase  is  one  of  the  three  forms  of  cellulase  enzymes, widely  used  in  different industries, and has been synthesized by animals, plants and microorganisms. β-glucanase is one of  the  feed enhancing enzymes, so adding of β-glucanase  to  the  feed originated  from plants,  it can not only enhance their nutritional quality greatly, but also resolve the digestion problems of chickens/pigs due to high amount of β-glucan in these kinds of feed. In  this work, β-glucanase gene  from A. niger was  ligated  in expression vector pESC-His and expressed in S. cerevisiae KY117. EglB gene was cloned in pCR2.1 vector, then ligated in expression vector pESC-His using T4 ligase enzyme after cleaving both recombinant pCR2.1/ EglB and pESC-His by BamHI and  XhoI.  Using  protoplast  fusion  method,  recombinant  pESC-His/EglB  was  transformed  into competent  S.  cerevisiae  KY117  strains.  Transformants  were  verifyed  by  PCR  using  specific primers GAL10 for pESC-His plasmid. Recombinant S. cerevisiae KY117 was cultured in SC-His and induced by galactose. Total protein  was  subjected  to  SDS-PAGE  and  the  obtained  result  showed  that  after  60  hours incubation,  the  protein with molecular weight  about  17kDa was  induced,  corresponding with theoretical EglB. Biological  activity  of  the  expressed  protein  was  tested  based  on  CMC-ase  activity  of recombinant  KY117.  The  strains  without  recombinant  plasmid  did  not  digest  CMC  in  the medium,  meanwhile  recombinant  S.  cerevisiae  KY117  made  clearly  unstained  circular  zone around the wells after staining CMC plates with Congo red